Kersen (Cherry) (Muntingia calabura L) Leaves as an Alternative Plant Free Radical Scavenger in Improving the Immune System - St. Maryam; Baits, Muzakkir; Tahir, Masdiana (Window of Health : Jurnal Kesehatan, 2023)
Kersen (Cherry) (Muntingia calabura L) leaves are empirically used to treat various diseases because they contain flavonoid and tannin compounds. Based on previous research, it was reported that phenolic compounds, tannins, and flavonoids can potentially counteract free radicals so that they can improve the body's immune system. The purpose of this study was to determine the antioxidant activity of extracts of methanol, ethyl acetate, and n-hexane from cherry leaves (Muntingia calabura L.). The DPPH free radical scavenging method is based on the reduction of the colored DPPH free radical methanol solution by free radical inhibition. The extraction process of a compound is carried out to separate the material from the mixture using a suitable solvent. The existence of a level of polarity of a solvent used to attract the components of active compounds in plants is a guide for the search for new compounds in a plant. The potential of a compound to counteract free radicals can be determined by calculating the IC50. The results showed that the extract of methanol, ethyl acetate, and n-hexane of the cherry leaf (Muntingia calabura L.) had inhibitory activity against DPPH free radicals with IC50 values of 8.67; 9,097, and 18.17 g/mL. Meanwhile, gallic acid has inhibitory activity with an IC50 value of 1.77 g/mL. Methanol and ethyl acetate extracts of cherry leaves were able to inhibit DPPH activity in a very strong category, which was almost comparable to gallic acid, while n-hexane extract had antioxidant activity in a strong category.